Samspel mellan arkitekter och konstruktörer under projekteringen - al Abdllawi,Sam (TVBP, 2019)
Contractors who start building based on incomplete documents will always require many costly solutions. The cost to correct mistakes in the beginning of the project is less than the cost to correct mistakes at the end of the project when the admission takes over. Factors that contribute to these large costs are in the planning stage, when transferring information and lack of communication. Collaboration and communication are important factors in creating a trusting relationship between the participants. The team spirit and the dynamic of a team are important in achieving common goals. Architects and structural engineers should therefore have a dialogue continuously and show each other trust and openness. The purpose of this study is to identify, analyze and an attempt to make the interaction more efficient between architects and structural engineers during the planning process, from a interdisciplinary perspective. The investigation of this study has been able to establish the underlying causes of the problems through interviews. Based on this, suggestions for improvements have been made, which can profit any company financially in the long term. The cause of these problems is due to the fact that all members of the team have different backgrounds and different corporate culture. With an inexperienced client who is unclear and prone to make changes and at the same time wants to build in the shortest possible time, as cheaply as possible while the result is as good as possible, requires that the project is managed with good coordination skills and communication skills. Many problems and misunderstandings can be eliminated when the planner is entering a project with collaboration skills and with the right attitude. With the right conditions, improvement suggestions can be applicable and get a breakthrough. Some improvement suggestions are easy to implement, while others require more time, energy and a greater investment. If more people get involved and show commitment to the project, the better the cooperation will be between architects and structural engineers in the planning phase of the building process.
Keywords: Samspel; samverkan; kommunikation; arkitekt; konstruktör; projektledare; projektering; projekteringsprocess; teamdynamik; partnering; erfarenhetsåterföring; engagemang. Interaction; collaboration; communication; architect; structural engineer; project manager; projection; projection process; team dynamics; feedback system; commitment.